2010
DOI: 10.1103/physrevlett.105.178302
|View full text |Cite
|
Sign up to set email alerts
|

Colloids in Cholesterics: Size-Dependent Defects and Non-Stokesian Microrheology

Abstract: We simulate a colloidal particle (radius R) in a cholesteric liquid crystal (pitch p) with tangential order parameter alignment at the particle surface. The local defect structure evolves from a dipolar pair of surface defects (boojums) at small R/p to a pair of twisted disclination lines wrapping around the particle at larger values. On dragging the colloid with small velocity v through the medium along the cholesteric helix axis (an active microrheology measurement), we find a hydrodynamic drag force that sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 29 publications
8
67
0
Order By: Relevance
“…To confront these difficulties, in the past decade, several hybrid simulation techniques [28][29][30][31][32] as well as other mesoscopic methods [33,34] for the dynamics of complex colloidal suspensions have been developed. Of these methods, we here adopt the fluid-particle-dynamics (FPD) method [30,31] to incorporate HIs into the study of a model active suspension.…”
Section: Methodsmentioning
confidence: 99%
“…To confront these difficulties, in the past decade, several hybrid simulation techniques [28][29][30][31][32] as well as other mesoscopic methods [33,34] for the dynamics of complex colloidal suspensions have been developed. Of these methods, we here adopt the fluid-particle-dynamics (FPD) method [30,31] to incorporate HIs into the study of a model active suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics. On the other hand, colloidal dispersions in twisted nematic and cholesteric LCs (CLCs) have received less attention [32][33][34][35][36][37][38][39][40][41][42][43][44] because of the complexity of the problem caused by, for example, the screening of elastic interactions by periodic structure of cholesterics. 44 This complexity increases as the ratio between the particle's size and cholesteric periodicity increases.…”
Section: Introductionmentioning
confidence: 99%
“…4), is also the ground state in cholesterics--the knots are metastable--although the difference in energies is small (of order 1-2%) and decreases both with increasing chirality and knot complexity p. The behavior with increasing p can be understood in terms of the total length of disclination line, which scales as p for the isolated loops and as ffiffiffiffiffiffiffiffiffiffiffiffi 4 + p 2 p for the knots. If the chirality is increased such that the pitch becomes smaller than the width of the colloid, then the disclinations develop twists analogous to those around spherical colloids (37,48).…”
Section: Möbius Strips and Knotted Defectsmentioning
confidence: 99%